2018
DOI: 10.23917/jramathedu.v3i2.6616
|View full text |Cite
|
Sign up to set email alerts
|

Developing Learning Trajectory Based Instruction of the Congruence for Ninth Grade Using Central Java Historical Building

Abstract: This research aims to produce a Learning Trajectory Based Instruction (LTBI) that can help the ninth grade students understand the concept of congruence of the two-dimensional shape by examining Lawang Sewu as one of Central Java historical buildings. LTBI is defined as a teaching and learning trajectory that uses Hypothetical Learning Trajectory (HLT) for instructional decisions. The present research uses the design research developed by Gravemeijer and Cobb that consists of three phases; the preliminary desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…Hal tersebut selaras dengan hasil penelitian Dewi, Khodijah, dan Setiawan (2020) yang menyatakan bahwa siswa terbukti termotivasi dengan digunakannya aplikasi GeoGebra pada konsep transformasi. Beberapa penelitian sebelumnya juga telah menggunakan konteks lokal dalam pembelajaran matematika yaitu motif kain batik Sidoarjo (Lestariningsih, 2017), bangunan bersejarah (Fahrurozi, et al, 2018;Nursyahidah, Saputro, & Albab, 2020), dan tradisi masyarakat (Aisyah, Nursyahidah, & Kusumaningsih, 2020;Nursyahidah, et al, 2021). Oleh karena itu, lintasan belajar dengan menggunakan konteks Klenteng Sam Poo Kong Semarang dapat menjadi salah satu alternatif dalam pembelajaran refleksi dan translasi.…”
Section: Pembahasanunclassified
“…Hal tersebut selaras dengan hasil penelitian Dewi, Khodijah, dan Setiawan (2020) yang menyatakan bahwa siswa terbukti termotivasi dengan digunakannya aplikasi GeoGebra pada konsep transformasi. Beberapa penelitian sebelumnya juga telah menggunakan konteks lokal dalam pembelajaran matematika yaitu motif kain batik Sidoarjo (Lestariningsih, 2017), bangunan bersejarah (Fahrurozi, et al, 2018;Nursyahidah, Saputro, & Albab, 2020), dan tradisi masyarakat (Aisyah, Nursyahidah, & Kusumaningsih, 2020;Nursyahidah, et al, 2021). Oleh karena itu, lintasan belajar dengan menggunakan konteks Klenteng Sam Poo Kong Semarang dapat menjadi salah satu alternatif dalam pembelajaran refleksi dan translasi.…”
Section: Pembahasanunclassified
“…IRME, which has been going on since 2001, has five main characteristics (Widyawati et al, 2016), namely the use of context, models, student contributions, linkages, and interactivity, that can facilitate students in understanding the concepts well. The use of IRME in this study is drawn upon the results of previous studies, which revealed that IRME could increase students' motivation in learning (Nursyahidah et al, 2018;Fahrurozi et al, 2018;Hartono et al, 2021), improve students' understanding (Sari et al, 2015), ease students to understand concepts (Fitri & Prahmana, 2018;Lestari et al, 2021), direct students' understanding from the informal stage to the formal stage, and create meaningful learning (Hartono et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it is crucial for the teacher to design meaningful learning to maximize the effectiveness and efficiency of learning, improve concept understanding, create meaningful learning, and achieve optimal learning objectives (Nursyahidah et al, 2021a) by choosing appropriate approaches. One of the approaches that are suitable for constructing a given concept using a familiar context to students and allow students to be active in learning (Kusumaningsih et al, 2020) is Indonesian Realistic Mathematics Education (IRME) (Nursyahidah et al, 2013(Nursyahidah et al, , 2018Fahrurozi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…IRME has been used since 2001. It can increase students' ability and motivation to solve problems (Nursyahidah et al, 2013(Nursyahidah et al, , 2018Fahrurozi et al, 2018) and can make students think critically and creatively so that it http://journals.ums.ac.id/index.php/jramathedu is easy to understand mathematical concepts using several things that are close to students (Simanulang, 2014;Fitri & Prahmana, 2018;2020;Kusumaningsih et al, 2019). In addition, this approach can create meaningful, effective, efficient, and fun learning objectives such as the ability to solve problems can be achieved (Nursyahidah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation